PENGARUH EDTA DALAM PENENTUAN KANDUNGAN TIMBAL DAN TEMBAGA PADA KERANG HIJAU (Mytilus viridis) - Ni Made Suaniti (Master Program of Environmental Science, Postgraduate Program of Udayana University)
Effect of addition Etylene Diamines Tetra Acetate (EDTA) on plumbum (Pb) and cuprum (Cu)contents in green mussel (Mytilus viridis) has been decreased their metal content . One part of sample wasdestructed with ten part of acid mixture. Using a mixture 10 mL sulphuric acid and 40 mL nitric acid conc.After destruction the sample was analysed using Atomic Absorption Spectrometry (AAS) with calibrationcurve method.Result showed that Pb contents found in dry green mussel was between 28.6128 - 29.8442 mg/kg andCu contents found in dry green mssel was between 2.4239 – 2.8858 mg/kg. After adding EDTA 0,1 M at pH 4for 30 minute the contents of Pb and Cu decreased. The content of Pb in dry sample decreased to 27.3829 -27.9988 mg/kg, while the content of Cu in in dry sample decreased to 0.2579 – 0.6919 mg/kg